GAMBARAN PENERAPAN HUKUMAN PADA ANAK USIA DINI OLEH PENDIDIK TAMAN KANAK-KANAK DI KECAMATAN TAMPAN KOTA PEKANBARU - Susan Nova Linda; Ria Novianti; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This objective of this research was to describe the application of punishment to children by teacher at Tampan Subdistrict Pekanbaru. Sample of this research are 68 teachers with education background from S1, DII, DI, and high school from Tampan Subdistrict Pekanbaru. Datas were gathered with quesioner that explane statemants about the application of punishment in children by the teacher at Tampan Subdistrict Pekanbaru. The conclution of this reserch that application of punishment to chidren by teacher at Tampan Tampan Subdistrict Pekanbaru on catagorie high (67,26%), while if it was looked of education degree of educator highest was apply of punisment to early childhood on S1 (70,45%) and lowest on D I (46,1%). This mean teacher was applied of punishment to childrens.Key Words : Punishment, Children